Contemporary occupational health nursing : a guide for practitioners - Thornbory, Greta (Routledge, 2014)
"Written by and on behalf of the Association of Occupational Health Nurse Practitioners (AOHNP). This textbook provides a practical guide for those training as, or practising within, occupational health nursing. Concerned with the health of the people at work and the effects of work on health and health on work, this distinctive branch of public health nursing requires specific knowledge and skills. Contemporary Occupational Health Nursing includes chapters on: Public Health, Leadership, Health Promotion and Protection, Health Surveillance, Health Assessment, Case Management and Rehabilitation, Mental Health, Management of Occupational Health Services, Epidemiology and Research and Quality Assurance and Auditing. Discussion of ethical issues is woven throughout and each chapter is written by an experienced occupational health practitioner and includes features such as case studies, activities, learning outcomes, chapter summaries and key point boxes. This book is designed as a text for those undertaking specialist community public health nursing qualifications and as an important resource for all nurses new to occupational health practice"--Resumé vydavatele.
Keywords: pracovní lékařství -- Velká Británie; nemoci z povolání; hygiena práce; ošetřovatelství; occupational medicine -- Great Britain; occupational diseases; industrial hygiene; nursing; učebnice; textbooks